Labor income risk, demographic risk, and the design of (wage-indexed) social security - Christoph Borgmann (Albert-Ludwigs-Universität Freiburg, Institut für Finanzwissenschaft, 2002)
Pay-as-you-go pension programs can help to share risk amongst generations. While a wage-indexed pension program is best suited to share labor income risk, I show that the combination of stochastic labor income and stochastic population growth may reduce the possibilities for intergenerational risk sharing: Labor income risk can only be shared when individuals are also exposed to demographic risk. For demographic uncertainty the usual categorization of pension programs does not suffice. I therefore introduce policies on how the demographic uncertainty is transmitted via social security. An optimal demographic indexation is derived for a small open economy and a closed economy.
urn:nbn:de:bsz:25-opus-18711
Keywords: 330; intergenerational risk sharing; social security; demography; Gesetzliche Rentenversicherung; Overlapping Generations; Einkommen; Bevölkerungsentwicklung; Risiko; Lohnindexierung; Lebenszyklus; Theorie